Training opportunities and the increase in the number of nurses in home-visit nursing agencies in Japan: a panel data analysis - Noriko Morioka; Suguru Okubo; Yoshie Yumoto; Yasuko Ogata (BMC, 2019)
Abstract Background A training opportunity in which ongoing education is encouraged is one of the determinants in recruiting and retaining nurses in home-visit nursing care agencies. We investigated the association between ensuring training opportunities through scheduled training programs and the change in the number of nurses in home-visit nursing agencies using nationwide panel data at the agency level. Methods We used nationwide registry panel data of home-visit nursing agencies from 2012 to 2015 in Japan. To investigate the association between planning training programs and the change in the number of nurses in the following year, we conducted fixed-effect panel data regression analysis. Results We identified 4760, 5160 and 5025 agencies in 2012, 2013, and 2014, respectively. Approximately 60-80% of the agencies planned training programs for all staff, both new and former, during the study period. The means and standard deviations of the percentage change in the number of full time equivalent (FTE) nurses in the following year were 4.2 (19.8), 5.7 (23.5), and 5.8 (25.1), respectively. Overall, we found no statistically significant association between scheduled training programs and the change in the number of FTE nurses in the following year. However, the associations varied by agency size. Results of analysis stratified by agency size suggested that the first and second quartile sized agencies (2.5-4.0 FTE nurses) with scheduled training programs for all employees were more likely to see a 9.0% (95% confidence interval [CI]: 4.5, 13.5) and 8.5% (95% CI: 2.4, 14.5) increase in the number of FTE nurses in the following year, respectively. Similarly, the first and second quartile sized agencies with scheduled training programs for new employees were more likely to see a 4.7% (95% CI: 2.1, 7.2) and 3.3% (95% CI: 0.4, 6.2) increase in the number of FTE nurses in the following year, respectively. Conclusions Ensuring training opportunities through scheduled training programs for all staff, both new and former, in relatively small-sized home-visit nursing agencies might contribute to an increase in the number of nurses at each agency.